2021
DOI: 10.1021/acs.jmedchem.1c00447
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin Neuropeptides Decrease Apparent Proton Affinity of ASIC1a by Occluding the Acidic Pocket

Abstract: Prolonged acidosis, as it occurs during ischemic stroke, induces neuronal death via acid-sensing ion channel 1a (ASIC1a). Concomitantly, it desensitizes ASIC1a, highlighting the pathophysiological significance of modulators of ASIC1a acid sensitivity. One such modulator is the opioid neuropeptide big dynorphin (Big Dyn) which binds to ASIC1a and enhances its activity during prolonged acidosis. The molecular determinants and dynamics of this interaction remain unclear, however. Here, we present a molecular inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…If correct, the ‘ECD only ’ state would be expected to affect the activity of other ECD-targeting ASIC1a modulators. To test this possibility, we turned to BigDyn, a neuropeptide that competes with PcTx1 for the binding site and induces a distinct closed state in ASIC1a ( Sherwood and Askwith, 2009 ; Borg et al, 2020 ; Leisle et al, 2021 ). The latter is indicated by a robust and distinct downward deflection of the K105C* fluorescence signal ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…If correct, the ‘ECD only ’ state would be expected to affect the activity of other ECD-targeting ASIC1a modulators. To test this possibility, we turned to BigDyn, a neuropeptide that competes with PcTx1 for the binding site and induces a distinct closed state in ASIC1a ( Sherwood and Askwith, 2009 ; Borg et al, 2020 ; Leisle et al, 2021 ). The latter is indicated by a robust and distinct downward deflection of the K105C* fluorescence signal ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Activate acid-sensing ion channels during stroke, facilitating acidosis and exacerbating neuronal death [86][87][88][89].…”
Section: Nocistatin Big Dynorphin and Rfamidementioning
confidence: 99%
“…The first example of this kind of neuropeptide was FMRFamide, which modulates Na + -selective ion channel opening in the snail cerebral neuron [ 85 ]. Since then, numerous studies have reported the direct and indirect regulation of acid-sensing ion channels by neuropeptides such as nocistatin [ 86 , 87 ], big dynorphin [ 88 ], and RFamide [ 89 ]. These neuropeptides are therefore of particular interest to researchers of stroke, as the activation of acid-sensing ion channels has been reported to facilitate acidosis and exacerbate neuronal death during ischaemic stroke [ 90 ].…”
Section: Function Of Neuropeptides In the Neurological Systemmentioning
confidence: 99%
“…It has been shown that Big Dyn and, with much lower potency (Table 1), Dyn A shift SSD curves of homomeric ASIC1a and heteromeric ASIC1a‐containing channels to higher proton concentrations, allowing the channels to remain in a closed state and available for activation during slight extracellular acidification (Fig. 3; Borg et al., 2020; Leisle et al., 2021; Sherwood & Askwith, 2009; Sherwood et al., 2011). In cultured neurons, this interaction promotes ASIC1a‐mediated neuronal death in response to slight but sustained acidification, similar to the conditions that occur during ischaemic stroke (Sherwood & Askwith, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An in silico molecular model of the interaction between Dyn A and ASIC1a suggested that the highly basic peptide inserts deep into the acidic pocket to occlude it (Leisle et al., 2021). Experiments using site‐directed mutagenesis of the peptide and the channel confirmed an extensive network of electrostatic interactions of acidic residues on ASIC1a and basic residues on Big Dyn (Borg et al., 2020; Leisle et al., 2021).…”
Section: Introductionmentioning
confidence: 99%